2010
DOI: 10.1212/wnl.0b013e3181d5275c
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in stroke outcome based on sex

Abstract: Objective: Stroke thrombolysis may have a differential effect by sex. We sought to examine the relationship between sex and outcome after thrombolysis. Variables including demographics, history, clinical data, process measures, and outcome were analyzed. The primary outcomes were the Stroke Impact Scale-16 score (SIS-16) and mortality at 6 months. We compared the outcomes of the thrombolyzed and nonthrombolyzed cohorts and examined the data for a tissue plasminogen activator (tPA)-by-sex interaction on the 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
5
33
0
Order By: Relevance
“…Increased assignment of tPA therapy to women should be encouraged as treatment outcomes do not differ between tPA treated men and women, while in non-tPA administered groups, males were more likely to have a better neurologic score as compared to women (Shobha et al 2010). This conclusion is also supported by data from endovascular intervention trials, where mechanical removal of the clot is performed to reestablish circulation in large vessel occlusion stroke.…”
Section: Stroke Therapeutics - Clinicalmentioning
confidence: 99%
“…Increased assignment of tPA therapy to women should be encouraged as treatment outcomes do not differ between tPA treated men and women, while in non-tPA administered groups, males were more likely to have a better neurologic score as compared to women (Shobha et al 2010). This conclusion is also supported by data from endovascular intervention trials, where mechanical removal of the clot is performed to reestablish circulation in large vessel occlusion stroke.…”
Section: Stroke Therapeutics - Clinicalmentioning
confidence: 99%
“…Previous reports have suggested that the impact of acute stroke thrombolysis on functional outcome is stronger in women than men [1,3,4,13], which if true, would have important clinical implications, as well as impact the design of future stroke treatment trials. However, this investigation, conducted in an observational population-based stroke study using PS methods to consider the influence of confounding factors by sex, found that the association of tPA with functional outcome was not different for women and men, partly due to sex differences in the confounding roles of age and stroke severity.…”
Section: Discussionmentioning
confidence: 99%
“…First, we fitted a conventional multivariable linear regression model regressing functional outcome (ADL/IADL score) on sex, tPA treatment status, the interaction between sex and tPA treatment status, age and NIHSS (Secondary Analysis 1). This model most closely reflects the multivariable approach used to address this research question in the existing observational literature [13]. Second, to evaluate the impact of our PS model approach to control for sex-specific confounding, we compared our results to those obtained from fitting the PS model but without any interactions with sex (only the sex main effect).…”
Section: Methodsmentioning
confidence: 99%
“…Although men and women may have comparable outcomes after treatment with tissue plasminogen activator, if untreated, women have poorer outcomes after acute stroke than men [63,64]. Women have a higher rate of cardioembolic strokes than thrombotic and lacunar strokes, with a higher frequency of atrial fibrillation as the etiology of their ischemic strokes.…”
Section: Acute Stroke Treatment and Outcomementioning
confidence: 99%